THE REPRESENTATION OF SHALOM MAWIRA'S RESISTANCE IN THE NOVEL PEREMPUAN YANG MENUNGGU DI LORONG MENUJU LAUT AND ITS RELEVANCE AS TEACHING MATERIAL - Adilla Wianti Sembiring, Adilla Wianti Sembiring; Esmeralda Estella br Sitepu, Esmeralda Estella br Sitepu; Nurul Hidayah, Nurul Hidayah; Sartika Sari, S.S.,M.Hum., Sartika Sari, S.S.,M.Hum.; Hilda Septriani, S.S.,M.Hum., Hilda Septriani, S.S.,M.Hum. (Universitas Negeri Semarang, 2024)
This study aims to analyze the representation of Shalom Mawira's resistance in the Novel